2023
DOI: 10.1002/lio2.1110
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Cochlear implantation in early‐deafened patients with Waardenburg syndrome: A systematic review and narrative synthesis

Abstract: ObjectiveThis systematic review aims to establish the expected hearing and speech outcomes following cochlear implantation (CI) in patients with profound congenital deafness secondary to Waardenburg syndrome (WS).MethodsA systematic review of the literature and narrative synthesis was performed in accordance with the PRISMA statement. Databases searched: Medline, Pubmed, Embase, Web of Science, Cochrane Collection, and ClinicalTrials.gov. No limits were placed on language or year of publication.ResultsSearches… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
(283 reference statements)
0
0
0
Order By: Relevance
“…At present, most studies show that patients with WS recover well after CI, but some studies still report that the postoperative effect on patients is not good ( 7 ). Lovett et al ( 2 ) compared the hearing and speech outcomes of WS patients before and after CI. The results showed that CI can be an effective way for improving the hearing and speech ability of WS patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, most studies show that patients with WS recover well after CI, but some studies still report that the postoperative effect on patients is not good ( 7 ). Lovett et al ( 2 ) compared the hearing and speech outcomes of WS patients before and after CI. The results showed that CI can be an effective way for improving the hearing and speech ability of WS patients.…”
Section: Discussionmentioning
confidence: 99%
“…Waardenburg syndrome (WS), discovered and named by Dutch physician Waardenburg in 1951 ( 1 ), is an autosomal dominant genetic disorder primarily characterized by auditory pigmentary abnormalities. Its key manifestations include inner canthus heterotopia, iris heterochrony, white hair on the forehead, and hereditary sensorineural deafness ( 2 ). WS is closely related to the abnormal migration and differentiation of melanocytes.…”
Section: Introductionmentioning
confidence: 99%